Gene expression changes in initiation and progression of oral squamous cell carcinomas revealed by laser microdissection and oligonucleotide microarray analysis. Issue 3 (20th July 2012) - Sumino, Jun; Uzawa, Narikazu; Okada, Norihiko; Miyaguchi, Ken; Mogushi, Kaoru; Takahashi, Ken‐Ichiro; Sato, Hiroaki; Michikawa, Chieko; Nakata, Yoshimi; Tanaka, Hiroshi; Amagasa, Teruo
Abstract Oral carcinogenesis is a complex process involving multiple genes. However, the genetic changes involved in this process are not apparent in identical oral squamous cell carcinomas (OSCCs). According to pathological characteristics, samples of normal tissue, oral dysplastic lesions (ODLs), and invasive cancers were obtained from identical OSCCs using laser microdissection (LMD). Large‐scale gene expression profiling was carried out on 33 samples derived from 11 OSCCs. We analyzed genes differentially expressed in normal tissues vs. ODLs and in ODLs vs. invasive tumors and identified 15 candidate genes with continuously increasing or decreasing expression during oral carcinogenesis. One of these genes, ISG15, was chosen for further characterization. Real‐time quantitative reverse transcription‐polymerase chain reaction and immunohistochemical analysis confirmed that ISG15 expression consistently increased during oral tumorigenesis. An ISG15 high‐expression level was significantly associated with poor prognosis (p = 0.027). In addition, patients with high‐expression tumors had a poorer 5‐year survival rate than patients with low expression levels (p = 0.019). In conclusion, we identified 15 genes with continuously increasing or decreasing expression during oral carcinogenesis. One of these, ISG15, is likely to be associated with both dysgenesis and tumorigenesis and may be a potential prognostic marker for oral cancer.